Litteraturens värden som diskurshistoriskt studiefält och analytisk terminologi: Inledningsanförande vid symposiet LITTERÄRA VÄRDEN OCH VÄRDERINGAR Karlstad 18–19 april 2024 - Mortensen, Anders (Tidskrift för litteraturvetenskap, 2025)
The Values of Literature as a discourse-historical field of study and an analytical terminology In this lecture, opening the Literary Values and Valuations symposium at Karlstad University in 2024, the paradoxes of ’literary value’ are examined in the contexts of their historical background in the tradition since the late 18th century of merging aesthetic and economic value, and the contemporary academic field of Economic Criticism. The rise of the so-called double discourse of value from early Romanticism onwards, as an ideologically biased opposition between materialist and humanist economies, still strongly affects everyday language and beliefs, and the modern concept of ’literary value’ is hampered by a number of inherent paradoxes which require historically informed scrutiny. What happens when scholars not only study the historical manifestations of value discourses, but also employ the highly contradictory concept of literary value as an analytical tool? A few remarks are also made in the lecture regarding the benefits and shortcomings of the discourse of literary value in comparison with other vocabularies of what is meritorious in literature in terms of taste, quality, or power.